Estabilidade estocástica de sistemas lineares com Saltos Markovianos e Sistemas Lineares com Saltos Semimarkovianos - Takamoto, Luana Hidemi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work, we present a study of Markov jump linear systems (MJLS) and Semi- Markov jump linear systems (S-MJLS). The MJLS are used to model systems subject to failures or abrupt changes in structure. Here, we study important results related to second moment stability of a continuous-time MJLS with infinite-time horizon. These results present necessary and sufficient conditions for stability of these systems and they also show that all second moment stability concepts are equivalent. In respect to S-MJLS, that represent a general case of MJLS, we present a study of stochastic stability of these continuous-time systems with infinite-time horizon. It means that we study a recent result that gives a sufficient condition for stochastic stability of this kind of system. As a contribution of this work, we introduce a study of second moment stability of a continuoustime MJLS, but now with horizon defined by a stopping time = TN associated with the accumulated N-th failure or repair periods, after which the system is brought to a halt for maintenance. Therefore, we adapt the second moment -stability concept and we present a result that gives necessary and sufficient conditions for -stability of these systems. Furthermore, we show that such conditions obtained are more restrictive than that associated with the infinite-time horizon. Finally, we also prove that all second moment -stability concepts are equivalent.

Neste trabalho, fazemos um estudo sobre os sistemas lineares com saltos markovianos (SLSM) e os sistemas lineares com saltos semimarkovianos (SLSS). Os SLSM sao utilizados para modelar sistemas sujeitos a falhas ou mudanças abruptas em suas estruturas. Nesta dissertaçao, estudamos importantes resultados sobre a estabilidade de segundo momento de um SLSM a tempo contínuo e com horizonte infinito. Tais resultados apresentam condiçoes necessarias e suficientes para a estabilidade destes sistemas e, alem disso, mostram que todos os conceitos de estabilidade de segundo momento sao equivalentes. Com relaçao aos SLSS, que representam um caso geral dos SLSM, apresentamos um estudo sobre a estabilidade estocastica de tais sistemas a tempo contínuo e com horizonte infinito. Mais especificamente, realizamos um estudo de um resultado recente que exibe uma condiçao suficiente para a estabilidade estocastica deste tipo de sistema. Como contribuiçao, introduzimos um estudo sobre estabilidade de segundo momento de SLSM a tempo contínuo, porem, com horizonte definido por um tempo de parada = TN associado ao N-ésimo momento de falha ou reparo, depois do qual o sistema e paralisado para manutençao. Desse modo, adequamos o conceito de estabilidade de segundo momento e apresentamos um resultado que exibe condiçoes necessarias e suficientes para a estabilidade destes sistemas. Alem disso, mostramos que tais condiçoes encontradas sao mais restritivas do que aquelas associadas ao horizonte infinito. Finalmente, provamos tambem que todos os conceitos de estabilidade de segundo momento sao equivalentes.
Keywords: Computação - Matematica; Sistemas lineares; Markov, Campos aleatórios de; Markov, Processos de; Computer science - Mathematics